GaClx- or GaAlClx-grafted Si-MCM-41: highly active and moisture insensitive/stable catalyst for the acylation and benzylation of benzene, naphthalene and substituted benzenes - Choudhary, Vasant R.; Jha, Rani (Applied Catalysis A-General, 2007)
GaClx- and GaAlClx-grafted Si-MCM-41 catalysts were prepared by reacting anhydrous GaCl3 and mixed anhydrous GaCl3 and AlCl3, respectively, with the terminal hydroxyl groups of Si-MCM-41 (pore size: 2.5 nm) in a dry non-aqueous reaction medium (CCl4) under reflux. The catalysts showed high activity for both the acylation and benzylation (with benzoyl chloride and benzyl chloride, respectively) of benzene, toluene, p-xylene, cumene, mesitylene, anisole and naphthalene. Both the catalysts are moisture insensitive or less moisture sensitive; the presence of moisture has a beneficial effect in the acylation over both the catalysts. The catalytically active sites of the GaClx-grafted Si-MCM-41 are (-O-)(2)GaCl (i.e. partially chlorided Ga anchored to Si through -O- linkage) species and the equivalent sites of the GaAlClx-grafted Si-MCM-41 are (-O-)(2)Ga(or Al)Cl and (-O-)(3)Ga(or Al) species. The high acylation/benzylation activities of both the catalysts even in the presence of moisture are attributed to their redox properties (Ga3+ -> Ga1+) rather than to their Lewis acid properties. After the grafting/chemical bonding, the grafted gallium chloride catalyst showed much higher acylation activity but lower benzylation activity than the physically deposited (on Si-MCM-41) or unsupported GaCl3. The GaAlClx-grafted Si-MCM-41 showed higher acylation activity than the GaClx-grafted Si-MCM-41, due to a synergetic effect of the Ga and Al species. However, the relative benzylation activity of the two catalysts showed strong dependence upon the presence or absence of electron donating group(s) and also upon the electron donating ability of the group(s) attached to the aromatic nucleus. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: acylation benzylation; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; moisture insensitive

Acylation of nitrobenzene and substituted nitrobenzenes by benzoyl chloride using GaClx- and GaAlClx-grafted meporous Si-MCM-41 catalysts - Choudhary, Vasant R.; Jha, Rani (Microporous and Mesoporous Materials, 2009)
A acylation of nitrobenzene and substituted nitrobenzene by benzoyl chloride can be accomplished with good yield in a short reaction period (<= 3 h), even in the presence of moisture, using GaClx- and GaAlClx-grafted mesoporous silica (Si-MCM-41) catalyst. The catalyst is reusable/environmentally friendly. The presence of moisture in the catalyst has beneficial effect on the acylation reaction. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Acylation; Benzoyl chloride; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; nitrobenzene